Exploring barriers to influenza vaccine uptake and recommendation among healthcare providers in the community in China: A qualitative study - Yuwei Liu; Ti Liu; Mingxiao Yao; Zengqiang Kou; Renpeng Li (Taylor & Francis Group, 2024)
Healthcare providers (HCPs) are recommended for priority influenza vaccination due to their high risk of contracting influenza. HCPs greatly aid in targeted population immunization campaigns. Therefore, understanding the factors that influence HCPs' decisions to get vaccinated and to recommend influenza vaccination is essential. However, there currently needs to be more evidence on this topic in China. Qualitative interviews using a semi-structured interview method were conducted with 180 HCPs from urban community hospitals and town hospitals in four cities in Shandong Province during August 2023. The interview content was analyzed using thematic analysis to identify the variables impacting the vaccination and recommendation practices of HCPs, as well as their suggestions for improving vaccination services. The results will help support the future development of precise intervention measures as well as focused education and training.